Development of Social Studies Textbooks Based on Environmental Education for JHS Grade VII - Arif, Syahrizal; Suprijono, Agus; Sunarto, Sunarto (The Indonesian Journal of Social Studies, 2021)
The PBLHS Movement Plan which was ratified as intended in article 7 of the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 52 of 2019 in paragraph 2 states the instructions for integrating the PBLHS movement in the One KTSP document. It is known that the textbooks used so far have not been able to support the PBLHS program, especially in Basic Competency 3.3 material so that learning occurs in class without going through a written document structure. This fact also shows that social studies learning through the PBLHS program is not well designed. This study aims to compile an Integrated Social Studies learning textbook PBLHS program with theme 4, namely "Dynamics of Human Interaction with the Environment". This study used a research and development (R&D) research design using a 4D models development model.